P371 1 YEAR OUTCOME OF BICARBON AORTIC MECHANICAL VALVE IN LOW–INR REGIMEN: RESULTS FROM SURE–AVR REGISTRY. (18th May 2022) - Santarpino, G; De Feo, M; Menicanti, L; Corbi, P; Nobre, A; Scardone, M; Luo, W; Rajakaruna, C; Nicoletti, A; Atzeni, F; Torella, M
Abstract: Background: The drawback of using mechanical valve is lifelong anticoagulation use, and close monitoring is required to prevent postoperative complications, including thromboembolism and anticoagulation–related bleeding. Moderate anticoagulation after mechanical heart valve replacement has been proposed to reduce these risks. The present study aimed to evaluate the safety and feasibility of reduced oral anticoagulation after Bicarbon aortic mechanical valve replacement. Methods: SURE–AVR is a propsective, multinational registry of patients undergoing aortic valve replacement. Between July 2018 and October 2020, among subjects undergoing AVR with Bicarbon valve in the SURE–AVR registry, 108 were assigned at discharge to low–INr regimen (international normalized ratio 1.5–2.5). Mean INr at discharge was 1.8+/–0.5 and 2.2+/–0.4 at 1 year. in–hospital and post–discharge outcomes up to 1 years were collected. The mean age was 55.5 +/–10.6 years old (range 25–82). Concomitant procedures included coronary artery bypass grafting (14.6%), mitral valve procedure (3.7%) and myectomy (1.9%). The follow–up duration averaged 1 year (361.8 +/– 258 days). Results: No bleeding events were reported in the late follow up. The low–INR regimen did not affect the thromboembolism rates, since no stroke or transient ischemic attack were reported post–operatively at each time point. No in–hospital or late deaths were reported among the 108 subjects analyzed. In the early period (<30 days), three reinterventions occurred: two because of postoperative bleeding requiring thoracotomy and one due to pericardial effusion. In the late postoperative period two reinterventions with device explant occurred (one for non–structural valve dysfunction and one for endocarditis (1.2%). Conclusion: The results of the SURE–AVr Registry demonstrated that the proposed Lower–INR Target is safe and feasible after Bicarbon aortic mechanical valve replacement. The low–intensity anticoagulation strategy is associated with a low risk of hemorrhagic events without any increase of thromboembolic complications.